Risk of Non-Alcoholic Fatty Liver Disease in Xanthelasma Palpebrarum - Chen HW; Lin JC; Wu YH; Chiu YL (Dove Medical Press, 2021)
Hsuan-Wei Chen,1 Jung-Chun Lin,1 Ying-Hsuen Wu,2,3,* Yi-Lin Chiu4,* 1Division of Gastroenterology, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 2Department of Ophthalmology, China Medical University Hospital, China Medical University, Taichung City, Taiwan; 3School of Medicine, College of Medicine, China Medical University, Taichung City, Taiwan; 4Department of Biochemistry, National Defense Medical Center, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Yi-Lin ChiuDepartment of Biochemistry, National Defense Medical Center, Taipei, TaiwanEmail yc566@georgetown.eduYing-Hsuen WuDepartment of Ophthalmology, China Medical University Hospital, China Medical University Email amywu0414@gmail.comBackground: Xanthelasma palpebrarum (XP) is a sign of hyperlipidemia and is closely linked to atherosclerosis. Since fatty liver shares similar risk factors with atherosclerosis, we hypothesized that patients with XP are also at risk of non-alcoholic fatty liver disease (NAFLD).Methods: In this retrospective cohort study, 37 patients with XP were compared with sex- and age-matched controls undergoing general health examination. Moreover, demographic information and lipid profiles were compared. The risk of NAFLD was evaluated using the hepatic steatosis and ZJU indices. In addition, we analyzed publicly available RNA sequencing data from the GSE48452 and GSE61260 datasets in the Gene Expression Omnibus database.Findings: Patients with XP had higher scores of hepatic steatosis index (37 ± 1.13 vs 32 ± 0.82, p=0.0006) and ZJU index (38.77 ± 1.0 vs 33.88 ± 0.74, p=0.0002). In addition, they had higher levels of lipid parameters, including total cholesterol, low-density lipoprotein (LDL), and fasting glucose. Among patients with fatty liver, individuals presenting with XP showed higher serum levels of total cholesterol (216 ± 10.4 vs 188.9 ± 7.6, p=0.04), fasting glucose (117.1 ± 6.4 vs 98.3 ± 2.4, p=0.002), and low-density lipoprotein (145.1 ± 8.7 vs 115.6 ± 6.4, p=0.009) than those without XP. In gene expression analysis, individuals presenting with non-alcoholic steatohepatitis showed higher Z scores of xanthelasma than those without non-alcoholic steatohepatitis.Conclusion: Our results suggest that individuals with XP have a higher risk of progression to NAFLD and develop a more severe dyslipidemia.Keywords: xanthelasma, xanthoma, fatty liver, NASH, NAFLD